Cooperational (Cooperational) Competence of Future Primary Teachers: Teamwork Skills (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In this article, the opinions about cooperation (cooperation) competence: teamwork skills of future primary school teachers are presented.